The treatment decision-making preferences of patients with prostate cancer should be recorded in research and clinical routine: a pooled analysis of four survey studies with 7169 patients - Ihrig, Andreas; Maatouk, Imad; Friederich, Hans-Christoph; Baunacke, Martin; Groeben, Christer; Koch, Rainer; Thomas, Christian; Huber, Johannes (Journal of cancer education, 2020)
Different patients want to take different roles in the treatment decision-making process; these roles can be classified as passive, collaborative, and active. The aim of this study was to investigate the correlation between decision-making preferences among patients with prostate cancer and personal, disease-related, and structural factors. In four survey studies, we asked 7169 prostate cancer patients about their decision-making preferences using the Control Preferences Scale (CPS) and collected clinical, psychological, and quality-of-life measures. Most patients (62.2%) preferred collaborative decision-making, while 2322 (32.4%) preferred an active role, and only 391 (5.5%) preferred a passive role. Age (p < 0.001), data collection mode (p < 0.001), peer-to-peer support (p = 0.018), treatment status (p < 0.001), performed or planned radical prostatectomy (p < 0.001), metastatic disease (p = 0.001), and quality of life (p < 0.001) showed significant associations with patients’ preferred decision-making roles. Oncologic risk group, anxiety, and depression were not significant in the model. In particular, younger prostate cancer patients with higher quality of life completing an online survey want to play a more active role in treatment decision-making. Before treatment has started, patients tend to prefer collaborative decision-making. Few prostate cancer patients in Germany prefer a passive role. These patients are mostly older patients, patients with a metastatic disease, and patients who have opted for prostatectomy. Whether this finding reflects a generational effect or a tendency by age group and disease phase should be investigated. Further research is also needed to describe the causalities of these relationships. The CPS offers valuable information for personal counselling and should be applied in clinical routine. In a large group of patients with prostate cancer, we found that there is a strong desire for joint decision-making with the physician before the actual treatment. Especially younger men, men with active online behaviour, and men with a high quality of life want to be actively involved in therapy decision-making processes.